2001
DOI: 10.1038/sj.ijir.3900678
|View full text |Cite
|
Sign up to set email alerts
|

General use of animal models for investigation of the physiology of erection

Abstract: Animals have consistently assumed a major place in the scienti®c developments of erection physiology, and in fact the use of animal models can be claimed to have inaugurated this ®eld as a true scienti®c discipline. The roots of the science of sexual medicine do not coincide with its practice, which conceivably pertains to aphrodisiacs and other sexual stimulants touted as therapies since antiquity. Rather, the beginnings of scienti®c study in the ®eld are ®ttingly identi®ed with the pioneering experimental wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…15,16,38 Although the animals possess similarities to humans with regard to the erectile function, normal or abnormal, comparative researches provide better comprehension of the similarities and differences about morphological structure and erectile function among the different species and in the human. 40 In this study, we observed a larger amount of elastic fibers in the rabbit penis than in human penis components, that is, CC, CS and TA. The literature points out that rabbits possess the morphological characteristics of a vascular penis, and therefore can be compared with humans.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…15,16,38 Although the animals possess similarities to humans with regard to the erectile function, normal or abnormal, comparative researches provide better comprehension of the similarities and differences about morphological structure and erectile function among the different species and in the human. 40 In this study, we observed a larger amount of elastic fibers in the rabbit penis than in human penis components, that is, CC, CS and TA. The literature points out that rabbits possess the morphological characteristics of a vascular penis, and therefore can be compared with humans.…”
mentioning
confidence: 67%
“…1,30 Elastic fibers are the major extracellular matrix components of the human fetal urethra 40 and their Vv in the CS increases in a linear fashion during fetal development (from 5.2% at 15th week to 14.8% at 36th week). In a young male, the elastic fiber Vv is about 19%.…”
mentioning
confidence: 99%
“…Studies have demonstrated that rodents are valid animal models for the investigation of erectile physiology and pharmacology (Burnett, 2001;Giuliano, 2001). Although rats have been widely used for in vivo and in vitro assessments of erectile function, the mouse model has recently become attractive due to the accessibility of genetic manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…Among the scientific tools used in animal models for the investigation of penile erection are the varied techniques they afford for stimulation and monitoring of erectile responses in vivo. 11 Erection monitoring methods have included many techniques. 11 Erection monitoring by observation and counting phenomenal erections is a widely used technique due to its simplicity and direct in vivo comparison.…”
Section: Introductionmentioning
confidence: 99%
“…11 Erection monitoring methods have included many techniques. 11 Erection monitoring by observation and counting phenomenal erections is a widely used technique due to its simplicity and direct in vivo comparison. 12,13 Because of high purchase and maintenance costs of large animals as well as their diminishing availability for medical research, small mammalian species such as lagomorphs and rodents have become the primary models.…”
Section: Introductionmentioning
confidence: 99%